AB0011 Evaluation of salivary mirnas in patients affected by sjÖgren's syndrome and correlation with clinical and ultrasonographic outcomes. (12th June 2018) - Talotta, R.; Biasin, M.; Bongiovanni, S.; Mercurio, V.; Vittori, C.; Boccassini, L.; Rigamonti, F.; Batticciotto, A.; Atzeni, F.; Trabattoni, D.; Sarzi-Puttini, P.
Abstract : Background: It has been demonstrated that miRNAs expressed in PBMCs and salivary glands of patients affected by Sjögren's Sydrome (SS) could be involved in the epigenetic control of the disease. Objectives: We aimed to compare the concentration of miRNA-146a/b, 16, 17–92 cluster and 181a in salivary and plasmatic samples collected from SS patients and healthy controls and to evaluate the associations with clinical, laboratory and ultrasound findings. Methods: We collected plasmatic and salivary samples from 28 patients (27 females, mean age 64.4±10.1 years, mean disease duration 10.7±6.9 years) affected by primitive SS according to ACR 2012 and/or 2016 criteria and 23 matched healthy controls. In the group of patients, the following data were recorded: ESSDAI and ESSPRI scores, anti-SSA and anti-SSB status and laboratory data, Schirmer's test, ultrasound scores of the four major salivary glands according to Cornec et al. and concomitant treatments. The following miRNA were extracted, retro-transcribed and quantified: miR16–5 p, miR17–5 p, miR18a-5p, miR19a-5p, miR19b-1–5 p, miR20a, miR92–5 p, miR146a-5p, miR146b-5p, miR181a-5p. Results: The concentration of miRNAs evaluated in plasma and saliva did not significantly match both in patients and in controls, underlining a different modulation in their expression according to the corporeal district. In patients and controls miRNAs16, 17 and 20 were hyper-expressed and miRNA146b and 181 hypo-expressed in salivary samples compared to plasmatic ones. Salivary miRNAs 18a and 146a were hyper-expressed in patients and hypo-expressed in controls, when compared to plasmatic concentrations. Comparing salivary and plasmatic patients' miRNAs concentrations to those of healthy subjects, plasmatic miRNA16 and 181a were significantly more expressed in patients than in controls (two-tailed Wilcoxon test and Student's T test for unpaired samples). In SS patients, salivary miRNA 181 and 146a were significantly increased in older subjects (p=0.01 and p=0.04 respectively). Spearman's correlation revealed that salivary miRNA146b was significantly hyper-expressed in patients with worse ESSPRI scores (p=0.02); on the contrary, salivary miRNA17, 146b and plasmatic miRNA17 were reduced in patients with higher scores at ultrasound evaluation (p=0.01, p=0.01 and p=0.04 respectively). Plasmatic concentration of miRNA18a was increased in patients with less lachrymal production at Schirmer's test (p=0.01) and plasmatic concentration of miRNA17 was reduced in patients with higher ESR values (p=0.01). Salivary miRNA18a was significantly increased in patients with anti-La/SSB (p=0.04; Mann-Whitney U test for unpaired samples). Salivary and plasmatic miRNAs did not correlate with disease duration and concomitant therapies. Conclusions: Our data show that the expression of salivary miRNAs 17, 18a and 146b may be altered in SS patients and associated with worse ultrasound and ESSPRI scores and anti-La/SSB positivity. Disclosure of Interest: None declared